Certain aspects of the implementation of imputed insurance of environmental risks in the Russian Federation - T. A. Belousova; N. V. Kirillova; V. S. Gudkovа; L. S. Krutova (Модернизация, инновация, развитие, 2024)
Purpose: of this article is to justify the implementation of insurance of environmental risks in the Russian Federation in the form of a pilot project based on imputed insurance with the definition of the main conditions of insurance coverage.Methods: the presented work uses statistical and predictive methods and the integrated approach for processing data on natural, climatic and human activity risks. Correlation-regression analysis and actuarial modeling were used to determine the conditions for insuring environmental risks and calculate tariff rates.Results: the paper substantiates the possibility of carrying out insurance of environmental risks in the form of a pilot project using an imputed form of insurance. Approaches to the calculation of the main parameters of business civil liability insurance for causing environmental damage as a result of an accident within the framework of a pilot project are proposed, including the determination of the minimum and maximum non-aggregate insurance limit, the minimum number of insurance companies, and the calculation of tariff rates. Due to the lack of Russian statistics on insurance coverage of environmental risks, statistical data on global insurance catastrophic losses from natural events, climate risks and human actions, as well as judicial statistics on disputes over the application of environmental protection legislation, were used for the calculation. The regions of the Russian Federation were identified for the implementation of a pilot project of environmental risk insurance.Conclusions and Relevance: the implementation of a pilot project of environmental risk insurance in certain regions on the basis of imputed insurance will make it possible to assess the current and forecast level of environmental risks in the Russian Federation, the need for insurance and reinsurance protection, the possibility and necessity of state participation in covering environmental damage. Using insurance statistics, insurers will be able to develop adjustment factors that encourage enterprises to take preventive measures. Reflection in a special reporting section of the results of the participation of insurance companies in the insurance of environmental pollution risks will be considered as the implementation of ESG principles.